Best to possibly not be: A prudential argument for antinatalism - Teo, Marcus T. L. (Bioethics, 2024)
This article starts by examining the present state of death ethics by attending to the euthanasia debate. Given that voluntary active euthanasia has seen strong support in the academic community, insights on the choiceworthiness of continued existence may be derived. Having derived cases of choiceworthy nonexistence (which I refer to as choiceworthy nonexistence [CNE] cases), I extend these intuitions to lives not worth starting, or choiceworthy nonexistence for potential people (which I refer to as foetal-CNE, or fCNE cases). Although I depart from Benatarian antinatalism by rejecting Benatar's claim that all existence is necessarily a harm, I posit a weaker argument that all existence is likely a harm since we cannot know until later in life if an existence is a harm. If I am right, then we have prudential reasons not to bear children, since they are more likely to suffer in lives not worth living than not.